Aneurysm of Upper Limb Arteries in Children: Report of Five Cases. (21st May 2020) - Nurmeev, Ildar; Osipov, Dmitry; Okoye, Bruce
Abstract : Background. Arterial aneurysm in children is rare. Aim . To present the description of case series of successful surgical treatment of upper limb aneurysms in children. The case series included 2 boys and 3 girls, with median age 3.3 years. One of them was a newborn with a true brachial artery aneurysm. Aneurysms were in the brachial ( n  = 3) and radial ( n  = 2) arteries. Two patients had idiopathic aneurysms. Two cases were associated with connective tissue dysplasia syndrome. One patient had a history of trauma. In 4 of 5 cases, there was a true aneurysm and in one a pseudoaneurysm. Diagnosis was carried out in all cases by using ultrasound, with arteriography in one case. All 5 children were operated on. Resection of the aneurysm and restoration of arterial patency was performed in 4 of 5 cases (ligation of the radial artery near the aneurysm in 1 case, aneurysm resection with end-to-end anastomosis in 1 case, resection with PTFE graft implantation in 1 case, and resection with implantation of an autovenous graft in 2 cases. Complications . Dysfunction and thrombosis of the PTFE graft required reoperation using an autovenous graft. Conclusion . Despite the rarity of the disease, timely and adequate surgical treatment of aneurysms of the arteries of the upper extremities in children is possible successfully in a specialized hospital.